Pharmacology, toxicology, and clinical use of new long acting localanesthetics, ropivacaine and levobupivacaine - Leone, S.; Di Cianni, S.; Casati, A.; Fanelli, G. (Acta Biomedica Atenei Parmensis, 2008)
Levobupivacaine and ropivacaine, two new long-acting local anesthetics, have been developed as an alternative to bupivacaine, after the evidence of its severe toxicity. Both of these agents are pure left-isomers and, due to their three-dimensional structure, seem to have less toxic effects on the central nervous system and on the cardiovascular system. Many clinical studies have investigated their toxicology and clinical profiles: theoretically and experimentally, some differences have been observed , but the effects of these properties on clinical practice have not been shown. By examining randomised, controlled trials that have compared these three local agents, this review supports the evidence that both levobupivacaine and ropivacaine have a clinical profile similar to that of racemic bupivacaine, and that the  minimal differences reported between the three anesthetics are mainly related to the slightly different anesthetic potency, with racemic bupivacaine > levobupivacaine > ropivacaine. However, the reduced toxic potential of the two pure left-isomers suggests their use in the clinical situations in which the risk of systemic toxicity related to either overdosing or unintended intravascular injection is high, such as during epidural or peripheral nerve blocks.